The antibacterial effects for Salmonella Enteritidis phage type 4 of different chemical disinfectants and cleaning agents tested under different conditions - Berchieri, A. [UNESP]; Barrow, P. A. (Taylor & Francis, 1996)
A selection of commercially available disinfectants, sanitizers and water sanitizers based on iodophor, quaternary ammonium compounds (QACs) and phenolic compounds were tested for their activity against a phage type 4 strain of Salmonella serotype Enteritidis in the presence of a variety of organic materials. In general the phenolic preparations were the most effective followed by the QACs and the iodophors. They were all inactivated to different degrees by chick fluff, chicken faeces, feed and wood shavings. The inactivation was greatest when Salmonella organisms were pre-dried in feed. Under these conditions formaldehyde and glutaraldehyde were still active. There was some evidence that induced resistance to stress conditions including culture at 42°C and anaerobic culture increased resistance to one of the water sanitizers.